Sensitization effect of kaempferol from persimmon leaves on HepG2 hepatoma cells with ABT-199 resistance and its molecular mechanisms - Chen, Li; Jiang, Xudong; Gao, Si; Liu, Xueping; Gao, Ying; Kow, Audrey Siew Foong; Tham, Chau Ling; Lee, Ming Tatt (Frontiers in Pharmacology, 2022)
ABT-199 (venetoclax) is the first-in-class selective B-cell lymphoma 2 (BCL2) inhibitor, which is known to be ineffective towards liver cancer cells. Here, we investigated the efficacy and the underlying molecular processes of the sensitization effect of kaempferol isolated from persimmon leaves (KPL) on the ABT-199-resistant HepG2 cells. The effects of various doses of KPL coupled with ABT-199 on the proliferation of HepG2 cells and on the H22 liver tumor-bearing mouse model were examined, as well as the underlying mechanisms. Our findings showed that ABT-199 alone, in contrast to KPL, had no significant impact on hepatoma cell growth, both in vitro and in vivo. Interestingly, the combination therapy showed significantly higher anti-hepatoma efficacy. Mechanistic studies revealed that combining KPL and ABT-199 may promote both early and late apoptosis, as well as decrease the mitochondrial membrane potential in HepG2 cells. Western blot analysis showed that combination of KPL and ABT-199 significantly reduced the expression of the anti-apoptotic proteins Bcl-2, Bcl-xL, and Mcl-1, raised the expression of Bax and cleaved caspase 3, and enhanced cytochrome C release and Bax translocation. Therefore, KPL combined with ABT-199 has a potential application prospect in the treatment of hepatocellular carcinoma.